Geographical and sectorial concentration in Czech, Hungarian and Slovak exports - Károly Attila Soós (Hungarian Academy of Sciences, Institute of Economics, 2015)
Statistical data display a high level of sectorial and geographical concentration in the exports of three Central European new member states of the European Union: the Czech Republic, Hungary and Slovakia. All the three export huge quantities of the products of certain sectors of engineering industries, and the main destination of their exports are the partner countries in the European Union. In this article, we discuss these issues in a comparative perspective, including into the analysis some other Central-Eastern European (CEE) new EU member states and also some other (non-CEE) EU member states. With more thorough examination we find that both kinds of concentration (which are also interrelated) are at lower levels than it appears in foreign trade statistics, and still rather high in international comparison. Concentration has both positive and negative (dangerous) sides.
Keywords: F13; F15; F23; F43; H25; J24; 330; external trade; international value chains; clustering; industrial structure; European Union; Central-Eastern Eutope; Hungary; Czech Republic; Slovakia; mechanical engineering; automotive industry